Analysis of the quality of biological laboratories of state senior high schools ini Majalengka regency in the academic year 2023/2024 - Mustofa, Romy Faisal; Ali, Mufti; Azzahra, Noni (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study This study aims to determine the quality of Public Senior High School biology laboratories in Majalengka Regency in the 2023/2024 academic year, especially in the aspect of room and laboratory managers. This research uses a qualitative method with a discrepancy evaluation model. The research was conducted in 4 Public Senior High School biology laboratories in Majalengka Regency. The research subjects in this study were the head of the laboratory, the head of facilities and infrastructure, biology subject teachers and representatives of students in grades XI and XII science class. The data collection techniques used by researchers were systematic observation, semi-structured interviews, and documentation. The research indicators in this study are the standardization of biology laboratory rooms and biology laboratory management. The results showed that the quality of the biology laboratory from the aspect of the room fell into a good category with an average percentage of 77.5%, while the management of the biology laboratory has not been done optimally and maximal.